Cognitive Processing Speed Is Strongly Related to Driving Skills, Financial Abilities, and Other Instrumental Activities of Daily Living in Persons With Mild Cognitive Impairment and Mild Dementia. (12th December 2020) - Wadley, Virginia G; Bull, Tyler P; Zhang, Yue; Barba, Cheyanne; Bryan, R Nick; Crowe, Michael; Desiderio, Lisa; Deutsch, Georg; Erus, Guray; Geldmacher, David S; Go, Rodney; Lassen-Greene, Caroline L; et al.
Abstract: Background: Cognitive processing speed is important for performing everyday activities in persons with mild cognitive impairment (MCI). However, its role in daily function has not been examined while simultaneously accounting for contributions of Alzheimer's disease (AD) risk biomarkers. We examine the relationships of processing speed and genetic and neuroimaging biomarkers to composites of daily function, mobility, and driving. Method: We used baseline data from 103 participants on the MCI/mild dementia spectrum from the Applying Programs to Preserve Skills trial. Linear regression models examined relationships of processing speed, structural magnetic resonance imaging (MRI), and genetic risk alleles for AD to composites of performance-based instrumental activities of daily living (IADLs), community mobility, and on-road driving evaluations. Results: In multivariable models, processing speed and the brain MRI neurodegeneration biomarker Spatial Pattern of Abnormality for Recognition of Early Alzheimer's disease (SPARE-AD) were significantly associated with functional and mobility composite performance. Better processing speed and younger age were associated with on-road driving ratings. Genetic risk markers, left hippocampal atrophy, and white matter lesion volumes were not significant correlates of these abilities. Processing speed had a strong positive association with IADL function ( p < .001), mobility ( p < .001), and driving ( p = .002). Conclusions: Cognitive processing speed is strongly and consistently associated with critical daily functions in persons with MCI in models including genetic and neuroimaging biomarkers of AD risk. SPARE-AD scores also significantly correlate with IADL performance and mobility. Results highlight the central role of processing speed in everyday task performance among persons with MCI/mild dementia.